Synthesis and Characterization of Celecoxib Derivatives as Possible Anti-Inflammatory, Analgesic, Antioxidant, Anticancer and Anti-HCV Agents - ŞENER, AZİZE; ÖZSAVCI, DERYA; BİNGÖL ÖZAKPINAR, ÖZLEM; ŞENKARDEŞ, SEVİL; KÜÇÜKGÜZEL, ŞÜKRİYE GÜNİZ (MDPI, 2013)
A series of novel N-(3-substituted aryl/alkyl-4-oxo-1,3-thiazolidin-2-ylidene)-4-[5-(4-methylphenyl)-3-(trifluoromethyl)-1H-pyrazol-1-yl] benzenesulfonamides 2a-e were synthesized by the addition of ethyl alpha-bromoacetate and anhydrous sodium acetate in dry ethanol to N-(substituted aryl/alkylcarbamothioyl)-4-[5-(4-methylphenyl)-3-(trifluoro-methyl)- 1H-pyrazol-1-yl] benzene sulfonamides 1a-e, which were synthesized by the reaction of alkyl/aryl isothiocyanates with celecoxib. The structures of the isolated products were determined by spectral methods and their anti-inflammatory, analgesic, antioxidant, anticancer and anti-HCV NS5B RNA-dependent RNA polymerase (RdRp) activities evaluated. The compounds were also tested for gastric toxicity and selected compound 1a was screened for its anticancer activity against 60 human tumor cell lines. These investigations revealed that compound 1a exhibited anti-inflammatory and analgesic activities and further did not cause tissue damage in liver, kidney, colon and brain compared to untreated controls or celecoxib. Compounds 1c and 1d displayed modest inhibition of HCV NS5B RdRp activity. In conclusion, N-(ethylcarbamothioyl)-4-[5-(4-methylphenyl)- 3-(trifluoromethyl)-1H-pyrazol-1-yl] benzenesulfonamide (1a) may have the potential to be developed into a therapeutic agent.
Keywords: anti-inflammatory; anticancer; celecoxib; hepatitis C NS5B; sulfonylthiourea; HEPATITIS-C VIRUS; HEPATOCELLULAR-CARCINOMA; POLYMERASE INHIBITORS; NS5B POLYMERASE; LIPID PEROXIDES; RING-SYSTEMS; PAW EDEMA; ACID; CYCLOOXYGENASE-2; PROSTAGLANDIN